2015
DOI: 10.1080/20477724.2015.1122852
|View full text |Cite
|
Sign up to set email alerts
|

Middle East respiratory syndrome coronavirus (MERS-CoV): animal to human interaction

Abstract: The Middle East respiratory syndrome coronavirus (MERS-CoV) is a novel enzootic betacoronavirus that was first described in September 2012. The clinical spectrum of MERS-CoV infection in humans ranges from an asymptomatic or mild respiratory illness to severe pneumonia and multi-organ failure; overall mortality is around 35.7%. Bats harbour several betacoronaviruses that are closely related to MERS-CoV but more research is needed to establish the relationship between bats and MERS-CoV. The seroprevalence of ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
126
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(136 citation statements)
references
References 100 publications
(153 reference statements)
2
126
0
Order By: Relevance
“…An earlier study in Saudi Arabia by Briese et al [18] showed that the whole genome sequence of viruses obtained from humans and camels were almost identical. It was suggested that the virus is transmitted to humans via direct contact with animals, especially dromedary camels in the Middle East [14,[19][20][21][22]. Human-to-human transmission is usually via direct contact with affected individuals and is higher among household and in healthcare settings [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study in Saudi Arabia by Briese et al [18] showed that the whole genome sequence of viruses obtained from humans and camels were almost identical. It was suggested that the virus is transmitted to humans via direct contact with animals, especially dromedary camels in the Middle East [14,[19][20][21][22]. Human-to-human transmission is usually via direct contact with affected individuals and is higher among household and in healthcare settings [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…[1] Such virus makes respiratory disease and leads a high level of mortality. [2] MERS-CoV was known to cause extreme viral pneumonia among individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Bat behaviour, including flying long distances, living in large colonies, having social interactions, and cohabitating with different bat species, favour the interspecies or intraspecies transmission of viruses (Calisher et al, 2006). During the last fifteen years, two Beta-CoVs, SARS-CoV and MERS-CoV, have jumped from bats to a mammalian intermediate host to humans (Field, 2009;Omrani et al, 2015). In addition, strains related to human Alpha-CoVs (HuCoV-229E, HuCoV-NL63) have been detected in bats, indicating the importance of the bat as a CoV reservoir (Pfefferle et al, 2009;Corman et al, 2015;Tao et al, 2017;Waruhiu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%